Impact Of Current Ratio (Cr) And Debt To Asset Ratio (Dar) On Return On Assets (Roa) at PT. Smart Tbk Period 2011-2020 - Sampurnaningsih, Sri Retnaning; Ikhsyan , Muhammad (ADPEBI, 2022)
The purpose of this study was to determine the effect of the current ratio (CR) and debt to asset ratio (DAR) on the Return on Assets (ROA) at PT SMART Tbk for the period 2011-2020. The research method used is descriptive quantitative and uses the classical assumption test, hypothesis testing (T-test and F-test), Coefficient of Determination test, with SPSS version 26 program. The result of the study is that the Current Ratio partially has no significant effect on ROA; Based on the results of the partial test (T-test), the CR variable with a value of t-count < t-table is 0.678 < 2.365 with a significant value of 0.519 > 0.05. Debt to Assets Ratio partially has no significant effect on Return on Assets; Based on the result of the partial test (T test), the DAR variable with a t-count value of 2.320 < t-table 2.365 with a significant value of 0.053> 0.05. Current Ratio and Debt to Assets Ratio simultaneously have a significant effect on Return on Assets, based on the result of F-test that F-count (5.453) > F-table (4.74) and the significant value is 0.037